If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2g + -8 = 10 + -4g Reorder the terms: -8 + 2g = 10 + -4g Solving -8 + 2g = 10 + -4g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '4g' to each side of the equation. -8 + 2g + 4g = 10 + -4g + 4g Combine like terms: 2g + 4g = 6g -8 + 6g = 10 + -4g + 4g Combine like terms: -4g + 4g = 0 -8 + 6g = 10 + 0 -8 + 6g = 10 Add '8' to each side of the equation. -8 + 8 + 6g = 10 + 8 Combine like terms: -8 + 8 = 0 0 + 6g = 10 + 8 6g = 10 + 8 Combine like terms: 10 + 8 = 18 6g = 18 Divide each side by '6'. g = 3 Simplifying g = 3
| X^2+7-9=0 | | 105*13/35*8/9 | | 5x-3.2=2x+2.8 | | 7x-91=2x-6 | | 32=17+x/2 | | 9x+10=3x+40 | | 48-2x=16x+24 | | F-2=3f+6 | | 5(x+3)+3(x-1)=-9 | | X/4+7=14 | | 21=(5x/6)+(3x/2) | | 2(x-4)+3(x+5)=2x | | 5.3q-1.9-4.6q=-0.3q-1.5 | | 2x-8+3x+18=2x | | 33/25*10/117*27/22 | | -2y+5x=-9 | | 62-9x=7x+18 | | x/3-26 | | 2x-5=57 | | x/2=48 | | x/4+x/3=7/4 | | 2f-7=43 | | x/6=15 | | x/2=46 | | 5c-11=19 | | 4x+14=112-10x | | 4x^2+3x-7=2x-2 | | 9-5p= | | 3b+7=52 | | 10r-12=-28 | | f=(g-h+k)/5 | | y=-2/2+2 |